Solve for ##u## and ##v## in the given equations

  • Thread starter chwala
  • Start date
In summary, the task is to find the values of the variables ##u## and ##v## that satisfy the provided equations.
  • #1
chwala
Gold Member
2,760
391
Homework Statement
See attached.
Relevant Equations
Understanding of simultaneous equations
1693395062637.png


In my approach i have:

##u-v=\dfrac{1}{6(u+v)}##

##\dfrac{1}{u+v} + 12(u+v)=8##

##1+12(u+v)^2=8(u+v)##

Let

##u+v=m##

then we shall have,

##12m^2-8m+1=0##

##m_1=\dfrac{1}{2}## and ##m_2=\dfrac{1}{6}##

Using ##m_2=\dfrac{1}{6}## and considering
##(u+v)(u-v)=\dfrac{1}{6}##
then,
##\dfrac{1}{6} (u-v)=\dfrac{1}{6}##

then we shall have the simultaneous equation,

##u-v=1##
##u+v=\dfrac{1}{6}## giving us
##u=\dfrac{7}{12} ⇒v=-\dfrac{5}{12}##

also using

##m_1=\dfrac{1}{2}##
then we shall have the simultaneous equation,
##u-v=\dfrac{1}{3}##
##u+v=\dfrac{1}{2}## giving us
##u=\dfrac{5}{12} ⇒v=\dfrac{1}{12}##

There may be another approach hence my post. Cheers.
 
  • Like
Likes Gavran
Physics news on Phys.org
  • #2
chwala said:
Homework Statement: See attached.
Relevant Equations: Understanding of simultaneous equations

There may be another approach
I would have started ##\frac 1{u+v}+\frac 2{u-v}=\frac{u-v+2(u+v)}{u^2-v^2}=(3u+v)6##.
No idea whether that is better.
 
  • Like
Likes Chestermiller and chwala
  • #3
haruspex said:
I would have started ##\frac 1{u+v}+\frac 2{u-v}=\frac{u-v+2(u+v)}{u^2-v^2}=(3u+v)6##.
No idea whether that is better.
@haruspex let me check that out...
 
  • #4
The other approach to this question though tedious

From,
##(u+v)(u-v)=\dfrac{1}{6}##

and noting that,

##3u-v=\dfrac{4}{3}## from the first equation then,

##(u+\dfrac{4}{3}-3u)(u+\dfrac{4}{3}+3u)=\dfrac{1}{6}##

...

##\dfrac{72u-16-72u^2}{9}=\dfrac{1}{6}##

##-432u^2+432u-96=9##

##432u^2-432u+105=0##

##144u^2-144u+35=0##

##u =\dfrac{144±\sqrt {20736-20160}}{288} ##

##= \dfrac{144±24}{288}##

##u_1=\dfrac{7}{12} ⇒v_1 = \dfrac{-5}{12}##

##u_2=\dfrac{5}{12} ⇒v_1 = \dfrac{1}{12}##
 
  • #5
You are given ##\frac 1{u+v} + \frac 2{u-v} = 8## and ##(u+v)(u-v) = \frac 16##. An apprach is...

Let ##x = u+v## and ##y = u-v##. Also maybe use symbols for the constants: with ##a=2, b=8,## and ##c = \frac 16## the equations become:

##\frac 1x + \frac ay =b## and ##xy = c##.

From the first one ##y + ax = bxy##. Since ##xy = c## this becomes ##y + ax = bc##.

Substituting ##y = bc~ – ~ax## into ##xy = c## gives a quadratic in ##x## and the rest should follow.

Replace ##a, b## and ##c## when convenient.

Edit: typo's fixed.
 
Last edited:
  • Like
Likes chwala
  • #6
With [itex]x = 1/(u + v)[/itex], [itex]y = 2/(u-v)[/itex] we have [tex]
x + y = 8 \quad xy = 12[/tex] so that [itex]x[/itex] and [itex]y[/itex] are the roots of [tex]
z^2 - 8z + 3 = (z - 4)^2 - 4 = 0[/tex] giving [itex]z = 4 \pm 2[/itex] and hence [tex]\begin{split}
(u,v) &= \left( \frac12\left(\frac1x + \frac2y\right), \frac12\left(\frac1x - \frac2y\right)\right) \\
&= \left( \frac 7{12}, -\frac{5}{12} \right) \quad\mbox{or}\quad \left( \frac{5}{12}, -\frac{1}{12}\right)\end{split}[/tex]
 
  • #7
pasmith said:
With [itex]x = 1/(u + v)[/itex], [itex]y = 2/(u-v)[/itex] we have [tex]
x + y = 8 \quad xy = 12[/tex] so that [itex]x[/itex] and [itex]y[/itex] are the roots of [tex]
z^2 - 8z + 3 = (z - 4)^2 - 4 = 0[/tex]
I think there's a typo' and the last equation should be
##z^2 - 8z + 12 = (z - 4)^2 - 4 = 0##

pasmith said:
giving [itex]z = 4 \pm 2[/itex] and hence [tex]\begin{split}
(u,v) &= \left( \frac12\left(\frac1x + \frac2y\right), \frac12\left(\frac1x - \frac2y\right)\right) \\
&= \left( \frac 7{12}, -\frac{5}{12} \right) \quad\mbox{or}\quad \left( \frac{5}{12}, -\frac{1}{12}\right)\end{split}[/tex]
Maybe I’ve made a mistake but it seems ##(u,v) = (\frac 5{12}, -\frac 1{12})## is not a solution...

##u+v = \frac 5{12} + \frac {-1}{12} = \frac 4{12} = \frac 13##

##u-v = \frac 5{12} - \frac {-1}{12} = \frac 6{12} = \frac 12##

##\frac 1{u+v}+ \frac 2{u-v} = \frac 1{\frac 13} + \frac 2{\frac 12} = 3+ 4 =7## (but it should be 8)

EDIT. I'm guessing it's just a sign-error so ##(u,v) = (\frac 5{12}, -\frac 1{12})## should be ##(u,v) = (\frac 5{12}, \frac 1{12})##.
 
Last edited:
  • Like
Likes haruspex
  • #8
pasmith said:
With [itex]x = 1/(u + v)[/itex], [itex]y = 2/(u-v)[/itex] we have [tex]
x + y = 8 \quad xy = 12[/tex] so that [itex]x[/itex] and [itex]y[/itex] are the roots of [tex]
z^2 - 8z + 3 = (z - 4)^2 - 4 = 0[/tex] giving [itex]z = 4 \pm 2[/itex]
Minor typo.

##\displaystyle z^2 - 8z + 3 = 0 \ ## should be ##\displaystyle z^2 - 8z + 12 = 0 \ ##

The rest follows from that without change.
 
  • Like
Likes chwala
  • #9
SammyS said:
Minor typo.

##\displaystyle z^2 - 8z + 3 = 0 \ ## should be ##\displaystyle z^2 - 8z + 12 = 0 \ ##

The rest follows from that without change.
Except that there is also the sign error in post #6 that @Steve4Physics noted in post #7.
 
  • Like
Likes SammyS
  • #10
chwala said:
In my approach i have:

##u-v=\dfrac{1}{6(u+v)}##

##\dfrac{1}{u+v} + 12(u+v)=8##

##1+12(u+v)^2=8(u+v)##

Let

##u+v=m##

then we shall have,

##12m^2-8m+1=0##

##m_1=\dfrac{1}{2}## and ##m_2=\dfrac{1}{6}##

Using ##m_2=\dfrac{1}{6}## and considering
##(u+v)(u-v)=\dfrac{1}{6}##
then,
##\dfrac{1}{6} (u-v)=\dfrac{1}{6}##

then we shall have the simultaneous equation,

##u-v=1##
##u+v=\dfrac{1}{6}## giving us
##u=\dfrac{7}{12} ⇒v=-\dfrac{5}{12}##

also using

##m_1=\dfrac{1}{2}##
then we shall have the simultaneous equation,
##u-v=\dfrac{1}{3}##
##u+v=\dfrac{1}{2}## giving us
##u=\dfrac{5}{12} ⇒v=\dfrac{1}{12}##
Good work.
 
  • Like
Likes chwala
  • #11
Defining ##x=u+v##, ##y=u-v## the second equation is ##xy=\frac 16##, or ##6x=1/y##.

Substituting into the first gives ##\frac 1{x}+12x=8##, which rearranges to ##12x^2-8x+1=0##. Hence ##x=1/2## or ##x=1/6##, with the corresponding ##y=1/3## or ##y=1##.

Since ##u## and ##v## are obviously ##\frac 12(x\pm y)##, then we have ##(u,v)=\left(\frac{5}{12},\frac{1}{12}\right)## or ##\left(\frac{7}{12},\frac{-5}{12}\right)##.
 
  • Like
Likes chwala

FAQ: Solve for ##u## and ##v## in the given equations

How do I solve a system of linear equations for ##u## and ##v##?

To solve a system of linear equations for ##u## and ##v##, you can use methods such as substitution, elimination, or matrix operations (like Gaussian elimination). These methods involve manipulating the equations to isolate one variable and then solving for the other.

What if the system of equations has no solution?

If the system of equations has no solution, it means the equations represent parallel lines that never intersect. This situation is referred to as inconsistent. You can determine this by finding that the determinant of the coefficient matrix is zero or by seeing that the equations lead to a contradiction.

Can I solve non-linear equations for ##u## and ##v##?

Yes, you can solve non-linear equations for ##u## and ##v##, but the methods are more complex compared to linear equations. Techniques include substitution, graphical methods, and numerical methods such as the Newton-Raphson method. Each method has its own set of steps and applicability depending on the nature of the non-linearity.

What is the role of the determinant in solving for ##u## and ##v##?

The determinant of the coefficient matrix in a system of linear equations helps determine whether the system has a unique solution. If the determinant is non-zero, the system has a unique solution. If the determinant is zero, the system may have no solution or infinitely many solutions.

How can I verify my solutions for ##u## and ##v##?

To verify your solutions for ##u## and ##v##, substitute them back into the original equations. If both equations are satisfied (i.e., both sides of each equation are equal), then the solutions are correct. This step ensures that the solutions work for the given system of equations.

Similar threads

Back
Top